OPTIMISME DENGAN PROBLEM FOCUSED COPING PADA MAHASISWA YANG SEDANG MENGERJAKAN TUGAS AKHIR - Gabriella Khriste Dea Valentsia; Sutarto Wijono (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2020)
This study aims to determine is there a relationship or not between optimism and problem focused coping. This research conducted on 2016 by Satya Wacana Christian University Faculty of Psychology students who did their final project with total 134 students using incidental sampling technique. Data collection methods used in this study use an optimism scale using an adaptation scale by Adilia (2010) which prepared referring to aspects of optimism from Seligman's theory (2001) namely the aspects of permanence, pervasiveness, and personalization aspects to measure the level of optimism in students who are currently do the final project and scale the problem focused coping using WCQ (Ways of Coping Questionnaire) owned by Folkman and Lazarus, 1988 to measure how students deal with or overcome problems that are sources of stress when completing the final project by finding various information. Data analysts used Product Moment and Pearson correlation tests, with results r = 0.647; p <0.05, so it can be concluded that there is a significant positive relationship between optimism and problem focused coping on students who are working on the final project.